(untitled) (International Journal of Multidisciplinary Research and Explorer, 2024)
This research paper presents a thorough examination of the collection of direct taxes spanning from the financial year 2017-18 to 2022-23. Direct taxes play a vital role in government revenue mobilization and economic governance, making it imperative to understand the trends, patterns, and implications associated with their collection. Through a comprehensive analysis of tax data, this study aims to shed light on the dynamics of direct tax collection over the specified period. By employing statistical techniques and empirical analysis, the paper identifies key trends, factors influencing tax collection, and their broader economic implications. The findings provide valuable insights for policymakers, tax authorities, and stakeholders, enabling them to formulate informed strategies for enhancing revenue mobilization, fostering economic growth, and ensuring fiscal sustainability.